Simulation study of stiffeners on composite plate - Asghar Zaidi, Mohd; Javed, M N; Kumari, Soni; Kumar, Ashish (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The present communication highlights a computational model to analyze the behavior of stiffened plates of such composite materials that is subjected to low velocity impact. The commercial explicit finite element software LS-Dyna has been used. The contact force is calculated in conjunction with the loading and unloading processes. The time history of the impact process such as target plate deflection, due to an impact force acting at the center of the plate, is obtained. Analysis shows the effect of number of stiffener on response of composite plate. In particular the displacement and contact force curve with respect to time were investigated, as the stiffness of the composite plate and contact force variation with time were analyzed without failure of composite structure with single and double stiffener. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->